Monocyte Subsets in Cardiovascular Disease: A Biomarker Perspective - Hristov, Michael; Weber, Christian (Thrombosis and Haemostasis, 2024)
Endothelial dysfunctions together with a dysregulated immune response and lipid accumulation are important confounding factors in the onset and chronic development of atherosclerosis. Recently, a large body of data has emerged on the sequential involvement of different immune cell types, including monocytes, in the pathology of this disease. In this condensed review, we aim to highlight some of the recent basic research and clinical findings on monocyte subsets published since our joint European Society of Cardiology consensus document, and re-evaluate their potential relevance as surrogate biomarkers in coronary artery disease.
Keywords: monocytes; atherosclerosis; leukocytes; activation